Negative Facial Expressions – But Not Visual Scenes – Enhance Human Working Memory in Younger and Older Participants - Belham, Flávia Schechtman; Tavares, Maria Clotilde H.; Satler, Corina; Garcia, Ana; Rodrigues, Rosângela C.; Canabarro, Soraya L. de Sá; Tomaz, Carlos (Frontiers in Pharmacology, 2017)
Many studies have investigated the influence of emotion on memory processes across the human lifespan. Some results have shown older adults performing better with positive stimuli, some with negative items, whereas some found no impact of emotional valence. Here we tested, in two independent studies, how younger and older adults would perform in a visuospatial working memory (VSWM) task with positive, negative and neutral images. The task consisted of identifying the new location of a stimulus in a crescent set of identical stimuli presented in different locations in a touch-screen monitor. In other words, participants should memorise the locations previously occupied to identify the new location. For each trial, the number of occupied locations increased until eight or until a mistake was made. In study 1, 56 younger adults and 38 older adults completed the task using images from the International Affective Picture System (IAPS). Results showed that, although younger adults outperformed older adults, no effects of emotion were found. In study 2, 26 younger adults and 25 older adults were tested using facial expressions as stimuli. Data from this study showed that negative faces facilitated performance and this effect did not differ between age groups. Taken together, our findings suggest that younger and older adults’ VSWM can be influenced by the emotional valence of the information, though this effect was present only for facial stimuli. Presumably, this may have happened due to the social and biological importance of such stimuli, which are more effective in transmitting emotions than IAPS images. Critically, our results also indicate that the mixed findings in the literature about the influence of aging on the interactions between memory and emotion may be caused by the use of different stimuli and methods. This possibility should be kept in mind in future studies about memory and emotion across the lifespan.